Creatural Frictions: The Trouble with Becoming-Animal: Review of David Herman, Creatural Fictions: Human-Animal Relationships in Twentieth- and Twenty-First-Century Literature - Bowen, Liz (Humanimalia, 2018)
David Herman, Creatural Fictions: Human-Animal Relationships in Twentieth- and Twenty-First-Century Literature. Palgrave Macmillan, 2016. 290 pp. 95 hc.